Oral Immunization with F4 Fimbriae and CpG Formulated with Carboxymethyl Starch Enhances F4-Specific Mucosal Immune Response and Modulates Th1 and Th2 Cytokines in Weaned Pigs - Benjamin Delisle; Carmen Calinescu; Mircea Alexandru Mateescu; John Morris Fairbrother; Eric Nadeau (Journal of Pharmacy & Pharmaceutical Sciences, 2012)
Purpose. F4 fimbriae are a potential candidate for an oral subunit vaccine for prevention of post-weaning diarrhea in swine due to infection with F4-positive enterotoxigenic Escherichia coli. However, large quantities of F4 fimbriae are required to induce a specific antibody response. The aim of the present study was to evaluate the effect of supplementation of F4 fimbriae with Cytosine-phosphate-Guanosine-oligodeoxynucleotide (CpG-A D19) or with complete cholera toxin (CT) as adjuvants on the F4-specific antibody response and cytokine production in weaned pigs following oral administration of F4 fimbrial antigen formulated with Carboxymethyl Starch (CMS). Methods. Oral dosage forms of F4 fimbriae alone or supplemented with CpG-A D19 or with CT were formulated with CMS as monolithic tablets, obtained by direct compression, and administered to weaned pigs. Blood and faecal samples were collected to determine the systemic and mucosal immune status of animals at various times until necropsy. During necropsy, contents of the jejunum and ileum were collected for determination of mucosal F4 specific antibodies. Segments of jejunum and ileum were also used to measure mRNA cytokine production. Results. The presence of CpG in the formulation of the fimbriae significantly increased F4-specific immunoglobulin (Ig) IgM and IgG levels in intestinal secretions, and enhanced Th1 (Interferon-gamma / IFN-γ, Tumour Necrosis Factor-alpha / TNF-α, Interleukin-12p40 / IL-12p40, IL-1β) and Th2 (IL-4, IL-6) cytokine production in intestinal tissues. Supplementation with CT did not result in induction of F4-specific antibodies in secretions, although a significant Th1 response (IFN-α, IFN-γ, IL-18) was detected in tissues. Neither F4-specific systemic antibodies, nor intestinally secreted IgA were detected throughout the immunization trial for all groups. Conclusions. CpG-A D19 appeared to be a promising adjuvant for an oral F4 subunit vaccine formulated with CMS excipient as monolithic tablets. This matrix afforded gastro-protection and delivered the F4 fimbriae at their intestinal sites.